Analysis of Clinical Presentations of Bruton Disease: A Review of 20 Years of Accumulated Data from Pediatric Patients at Severance Hospital - Chun, Jin-Kyong; Lee, Taek Jin; Song, Jae Woo; Linton, John A; Kim, Dong Soo (Yonsei medical journal, 2008)
X-linked agammaglobulinemia (XLA) is a humoral immunodeficiency disease caused by a mutation in the Bruton tyrosine kinase (BTK) gene resulting in defective B cell differentiation. Because it is a relatively rare disorder, it is difficult for clinicians to have a comprehensive understanding of XLA due to a lack of exposure to the disease. Clinical presentations of patients with XLA were analyzed and discussed to improve care plans. During a 20 year period, from January 1987 to June 2006, a total of 19 patients were diagnosed as XLA in the Department of Pediatrics at Severance Hospital, Seoul, Korea. A retrospective analysis of the clinical presentations of those patients was performed. The mean age of the XLA patients included in the study was 4.89 years, with a range of 6 months to 13 years. Twelve patients were diagnosed before age 5, while the other 7 patients were diagnosed after age 5. Recurrent infections observed in the patients included pneumonia, acute otitis media, septic arthritis, skin infection, sepsis, sinusitis, acute gastroenteritis, cervical lymphadenitis, epididymitis, meningitis, osteomyelitis, urinary tract infection and encephalitis. Frequency of admissions was variable from 0 to 12 times, depending on the time at which immunoglobulin therapy was started. Six cases had family histories positive for XLA. BTK gene mutations were found in 8 cases. The overall prognosis of XLA is good as long as patients are diagnosed and treated early with regular intra venous gamma globulin therapy before the sequelae of recurrent infections appear.